(untitled) (JED (Jurnal Etika Demokrasi), 2025)
The urgency of this research departs from the growing inequality between those most affected by climate change and those most responsible for it, particularly among Indonesia’s coastal communities who face severe ecological degradation, livelihood loss, and violations of environmental rights despite limited contribution to greenhouse gas emissions. This study aims to analyze the extent to which environmental rights for coastal communities are fulfilled within Indonesia’s legal and policy framworks and to identify the structural and regulatory barriers that hinder the realization of climate justice. The research employs a qualitative socio-legal approach using document studies sourced from statutory regulations, scholarly articles, and government reports, analyzed through normative legal interpretation and thematic analysis to integrate legal and social perspectives. The findings show that although environmental rights are constitutionally and statutorily recognized, their implementation remains fragmented due to regulatory disharmony, weak institutional coordination, and economic dependence on extractive industries, which collectively perpetuate systemic rights violations and climate inequality. These results imply that achieving climate justice requires coherent regulation, institutional reform, and participatory environmental governance. The novelty of this research lies in its integration of socio-legal analysis that connects normative legal guarantees with the lived realities of vulnerable communities, an approach rarely applied in previous studies. This study contributes theoretically and practically by offering a policy-oriented framework for developing participatory and justice-based climate governance and proposing the establishment of a dedicated Climate Change Law to protect coastal populations.